2017
DOI: 10.1111/inr.12375
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses' perceptions regarding nurse‐led antiretroviral therapy initiation in Hhohho region, Swaziland

Abstract: The study findings have implications for both the practice of the NARTIS programme and health policy development. The development of a health policy that alleviates the barriers to the NARTIS programme can enhance nurses' role and make care provision to people living with HIV/AIDS more effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…The search strategy used achieved an initial retrieval of 11,031 potential articles for the study, out of which 32 articles were finally included in the final sample (Table 1 Once the 32 selected studies had been evaluated (Table 1), it was observed that more than half of the articles stemmed from the Americas: Canada (3,35), The USA (1, 23-30, 34, 37, 45), Brazil (47) and one article that refers to the American continent in general (3); the rest of the evidence is distributed across studies from Asia (10, 14,32,38,40,40,42,43,43,44,49), Europe (39,41,46), Oceania (6,31,48), and Africa (33); therefore, all the articles are written in English. Regarding the journals where these articles were published, it was noted that all were published in journals indexed in the Proquest, Scopus, and Pubmed databases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search strategy used achieved an initial retrieval of 11,031 potential articles for the study, out of which 32 articles were finally included in the final sample (Table 1 Once the 32 selected studies had been evaluated (Table 1), it was observed that more than half of the articles stemmed from the Americas: Canada (3,35), The USA (1, 23-30, 34, 37, 45), Brazil (47) and one article that refers to the American continent in general (3); the rest of the evidence is distributed across studies from Asia (10, 14,32,38,40,40,42,43,43,44,49), Europe (39,41,46), Oceania (6,31,48), and Africa (33); therefore, all the articles are written in English. Regarding the journals where these articles were published, it was noted that all were published in journals indexed in the Proquest, Scopus, and Pubmed databases.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the evidence also reports that there are enabling factors for the performance of the role, firstly, when it is considered that these professionals provide "constructive" support with their work (38); in addition, they are resilient, capable of self-care and adaptability towards the continuous changes in protocol and scarcity of resources (42), as well as their capacity for planning, support, information, active participation in research and adequate use of resources (39), relevant aspects that should be considered by the employers of healthcare services, since they must ensure clear practices in the care to be provided, control measures for infections and personal protection equipment that is adequate for the use of healthcare providers, which are all indispensable variables to en-sure the health of healthcare providers and their families (28); in addition, the need for psychological support for these professionals is also evident (48), as well as the need for their continuing education. This need should not only satisfy nurses but also other healthcare providers who are for the implementation of programs and protocols with the objective of minimizing cross-infection for patient and staff safety in the face of a pandemic (10, 33,48), strengthening interdisciplinary work (46). One strategy reported in this review that will undoubtedly support their performance in improving communication with isolated populations is telehealth.…”
Section: S14mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, sustained support is necessary to ensure effective execution of the ART programme in resource-limited settings (Mavhandu-Mudzusi, Sandy, & Hettema, 2017). Nurses in Lesotho have reported the need for more supportive regular and sustained training on ART so as to keep abreast with the management of HIV (Nyangu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to provide better care and treatment for ART patients, it is of utmost importance for more capacity building to reduce existing gaps (Smith et al, ). Furthermore, sustained support is necessary to ensure effective execution of the ART programme in resource‐limited settings (Mavhandu‐Mudzusi, Sandy, & Hettema, ). Nurses in Lesotho have reported the need for more supportive regular and sustained training on ART so as to keep abreast with the management of HIV (Nyangu, ).…”
Section: Introductionmentioning
confidence: 99%